2015
DOI: 10.2174/2212798407666150401104716
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Composition and Antioxidant Activities of 6 New Turmeric (Curcuma Longa L.) Accessions

Abstract: The phytochemical composition and antioxidant capacities of 6 new NRCRI turmeric (Curcuma longa L.) accessions (39, 35, 60, 30, 50 and 41) were determined using standard techniques. The moisture contents of the tumeric samples ranged from 15.75 to 47.80% and the curcumin contents of the turmeric samples fell within the range of curcumin obtained from turmeric in other countries of the world. Furthermore, the turmeric accessions contained considerable amounts of antioxidants (measured using 2,2-diphenyl-1-picry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…longa (luyang dilaw) grown in Nigeria and Bangladesh and P. umbellatum (kamamba) variety in Pennsylvania, USA were reported with significant reducing power. 23,[26][27] Z. officinale (luya) rhizome showed significant ferric ion reduction (76.24% reduction) even at the lowest concentration of 12.79 µg/mL, which agrees with the reducing potencies of reference standards as shown: Trolox > BHT > Ginger > α-tocopherol. [28][29] Potential plant materials, D. esculentum (pako) leaves and D. philippinensis (katmon) fruit, showed effective reductive activity of 70.56±6.6% and 68.36±11.6% at 50.9 µg/mL and 36.77±12.8% and 44.53±23.1% at 12.7 µg/mL, respectively.…”
Section: Ferric Reducing Antioxidant Power (Frap) Assaysupporting
confidence: 81%
“…longa (luyang dilaw) grown in Nigeria and Bangladesh and P. umbellatum (kamamba) variety in Pennsylvania, USA were reported with significant reducing power. 23,[26][27] Z. officinale (luya) rhizome showed significant ferric ion reduction (76.24% reduction) even at the lowest concentration of 12.79 µg/mL, which agrees with the reducing potencies of reference standards as shown: Trolox > BHT > Ginger > α-tocopherol. [28][29] Potential plant materials, D. esculentum (pako) leaves and D. philippinensis (katmon) fruit, showed effective reductive activity of 70.56±6.6% and 68.36±11.6% at 50.9 µg/mL and 36.77±12.8% and 44.53±23.1% at 12.7 µg/mL, respectively.…”
Section: Ferric Reducing Antioxidant Power (Frap) Assaysupporting
confidence: 81%
“…e bioactive components present in turmeric volatile oil include tumerone that is reported to be effective against carcinogenesis. e previous investigation indicated that turmeric had distinctive antioxidant potential [64]. Curcumin removed turmeric oleoresin which is the resource material for the production of curcumin and contains oil, resin, and nonextractable curcumin.…”
Section: Antioxidant and Anti-inflammatory Activitymentioning
confidence: 99%
“…In traditional medicine, it usually serves to treat liver disorders including liver fibrosis. Turmeric possesses antiviral (Kim et al, 2009), anti-inflammatory (Bereswill et al, 2010), antioxidant (Al-Jassabi et al, 2012;Chinedum et al, 2015;Tanvir et al, 2017), antidiabetic (Aziz et al, 2013) and anticancer (Abdel-Lateef et al, 2016) properties. Liver is one of the important organs of the body which plays a major role in the metabolism of proteins, carbohydrates, lipids.…”
Section: Introductionmentioning
confidence: 99%